2013
DOI: 10.1111/j.1742-9552.2012.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate clinical psychology students' perceptions of an Acceptance and Commitment Therapy stress management intervention and clinical training

Abstract: Background Research into stress management interventions for clinical psychology trainees (CPTs) is limited, despite evidence indicating that these individuals are at risk for elevated stress, which can negatively impact personal and professional functioning. This study explored: (1) CPTs' perceptions of a previously evaluated Acceptance and Commitment Therapy (ACT) stress management intervention; and (2) their satisfaction with clinical training and suggested programme changes. Methods Fifty‐six postgraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
(92 reference statements)
2
17
0
Order By: Relevance
“…Findings support the interweaving of training in therapy competencies and self‐care skills via a self‐as‐laboratory approach within an ACT framework. The foundation for such training should be experiential learning and demonstration, which is consistent with published data on CPTs' suggested improvements for clinical psychology training (Pakenham & Stafford‐Brown, ; Scott, Pachana, & Sofronoff, ). The course described in this study provides a prototype for how training in ACT competencies and self‐care skills can be delivered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings support the interweaving of training in therapy competencies and self‐care skills via a self‐as‐laboratory approach within an ACT framework. The foundation for such training should be experiential learning and demonstration, which is consistent with published data on CPTs' suggested improvements for clinical psychology training (Pakenham & Stafford‐Brown, ; Scott, Pachana, & Sofronoff, ). The course described in this study provides a prototype for how training in ACT competencies and self‐care skills can be delivered.…”
Section: Discussionmentioning
confidence: 99%
“…ACT processes mediated the intervention effects on distress, self‐compassion, and counseling self‐efficacy. Further, qualitative data showed that most participants reported the application of ACT strategies personally and professionally, and an intention to continue using these in both areas (Pakenham & Stafford‐Brown, ).…”
mentioning
confidence: 99%
“…Groups based on ‘third‐wave’ cognitive–behavioural approaches, which aim not at removing stress but rather at fostering a different way of relating to it, have been found to be effective in managing trainee stress. These include mindfulness‐based stress reduction groups for trainee therapists (Shapiro et al ., ) and acceptance and commitment therapy groups for clinical psychology trainees (Pakenham & Stafford‐Brown, ; Stafford‐Brown & Pakenham, ). Groups based on compassionate mind theory (Gilbert, ) may be helpful for high achieving, perfectionist trainees whose drive and threat affect systems that may be overactive relative to their soothing affect system.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting self‐care during training provides career‐sustaining skills that can prevent burnout across all career phases. Preliminary data suggest that incorporating self‐care into a postgraduate psychotherapy curriculum using SP/SR promotes self‐care behaviours during training and confidence in maintaining them in later career (Pakenham, ; ; ; Pakenham & Stafford‐Brown, ). However, explicit instruction in self‐care is lacking in undergraduate psychology programs (Pakenham & Stafford‐Brown, ; Wise, Hersh, & Gibson, ).…”
Section: Introductionmentioning
confidence: 99%